2022
DOI: 10.1007/s40883-022-00271-0
|View full text |Cite
|
Sign up to set email alerts
|

Advancement of Organoid Technology in Regenerative Medicine

Abstract: Purpose Organoids are three-dimensional cultures of stem cells in an environment similar to the body’s extracellular matrix. This is also a novel development in the realm of regenerative medicine. Stem cells can begin to develop into 3D structures by modifying signaling pathways. To form organoids, stem cells are transplanted into the extracellular matrix. Organoids have provided the required technologies to reproduce human tissues. As a result, it might be used in place of animal models in scient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 143 publications
(346 reference statements)
0
10
0
Order By: Relevance
“…The emergence of ISCs and iPSCs represents a promising avenue for future research, and clinical trials will be conducted gradually. 115 , 116 Recently, the research team at Tokyo Medical and Dental University has reported the successful transplantation of the world’s first “organoid” into the intestinal mucosa of a refractory UC patient, marking the beginning of the organoid SC era. The team collected normal intestinal mucosa (including ISCs) from the patient under endoscopy, cultured it in vitro for approximately 1 month, and constructed an “organoid” with a diameter of 0.1–0.2 mm.…”
Section: Therapeutic Effects Of Scs In Ibdmentioning
confidence: 99%
“…The emergence of ISCs and iPSCs represents a promising avenue for future research, and clinical trials will be conducted gradually. 115 , 116 Recently, the research team at Tokyo Medical and Dental University has reported the successful transplantation of the world’s first “organoid” into the intestinal mucosa of a refractory UC patient, marking the beginning of the organoid SC era. The team collected normal intestinal mucosa (including ISCs) from the patient under endoscopy, cultured it in vitro for approximately 1 month, and constructed an “organoid” with a diameter of 0.1–0.2 mm.…”
Section: Therapeutic Effects Of Scs In Ibdmentioning
confidence: 99%
“…As organoids carry the genetic information of the source, they hold great potential for biomedical research and preclinical drug testing [ 3 ]. In the future, it is expected that human organoids will become one of the major sources of personalized regenerative medicine, gene repair, and transplantation therapy [ 4 , 5 ]. In theory, human organoids can be created from any organ and used in both basic and clinical research [ 2 ].…”
Section: Human Organoidsmentioning
confidence: 99%
“…An endogenous ECM must be produced to be used as a biomaterial for hepatocytes. Also, 3D structures must be supported, and the key features of stiffness, protein composition, and angiogenesis characteristics must be at least partially reproducible [ 52 ]. Using these biomaterials allows cells to be transplanted directly into the liver without going through the hepatic portal vein, resulting in more cells being transferred to the liver regeneration site.…”
Section: Advantages Of 3d Cultures In Studies On the Liver Metabolismmentioning
confidence: 99%